Reduction lead metal in process marinating local food fish pendap using lemon juice (citrus limon) - Asti, Nora Ayudi; Johan, Henny; Parlindungan, Deni; Primairyani, Ariefa; Defianti, Aprina; Nursaadah, Euis (JPBIO (Jurnal Pendidikan Biologi), 2025)
Fish have the potential to be contaminated with heavy metals such as lead, which can originate from human activities, industry, and ports. The Bengkulu people have a traditional processing method that is believed to reduce heavy metal content in fish through the immersion of fish in Pendap dishes using water and lemon. This study aims to observe the reduction of heavy metal content in fish during the immersion process using water and lemon juice in Pendap dishes. The research was experimental with positive and negative results and analyzed using the SPSS ANOVA test to see significant differences between treatment groups. The fish used as samples included Tongkol Sarda orentalis, Kembung Rastrelliger kanagurta, Tuna Thunnus albacares, and Tenggiri Scomberomorus Lacepède. The parts of the fish that were analyzed included the muscles, liver, and gills. All samples were exposed to Pb(NO3)2 and divided into 3 treatment groups: 1 positive control, 2 precipitated with water, and 3 precipitated with lemon juice (Citrus limon). The samples were tested using the reagents NaOH, KI, NH4OH, and HCl. Based on the research results, it was found that the application of lemon juice produced significant results in reducing Pb levels, as indicated by the negative test results.